Preservation of beauveria bassiana (balsam) vuillemin (moniliales: moniliaceae) pathogenicityagainst the coffee borer in different systems (2001)
The objective of this study is to find preservation techniques of Beauveria bassiana pathogenicity in the laboratory. Long term storage of B. bassiana cultures is very important to prepare industrial products. Preservation techniques for pathogenicity would replace the need to pass B. bassiana spores frequently in the target insect. Studies on B. bassiana pathogenicity are almost nonexistent. Viability of B. bassiana was evaluated in comparison with pathogenicity when subjected to different preservation temperatures with various protectors. The most succesful procedures were silica gel and mineral oil in refrigeration; glicerol and dimethilsulfoxide in liquid nitrogen; liophilization with skim milk at 10% and 20% and skim milk with inositol at 5%. The tests were carried our during 24 weeks at 6 weeks intervals. A monosporic B. bassiana culture (Bb. 9620) isolated by Cenicafé research center was used for the study. The mean value for the preservation of pathogenicity was influenced by the protectors used.